The mentor connection - Zey, Michael G. (Homewood, Ill. : Dow Jones-Irwin, 1984)
The Mentor Connection is an exciting view about mentoring and it effects to people's carriers and development.
Includes bibliographical references and index.
rua 30/05/17
Loan
Keywords: Mentoring in business; Success in business